2017
DOI: 10.1016/j.ejvs.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Inflow Artery and Tourniquet Derived Cephalic Vein Diameters on Predicting Successful Use and Patency of Arteriovenous Fistulas for Haemodialysis

Abstract: Among patients undergoing radiocephalic AVFs, a tourniquet derived cephalic vein diameter <4.3 mm was the single independent predictor of inferior secondary and functional secondary patency. Among patients undergoing brachiocephalic AVFs, all patency rates were inferior in the presence of a brachial artery diameter ≤4.1 mm and secondary patency was inferior in the presence of multiple risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
39
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 22 publications
0
39
1
Order By: Relevance
“…7 The present study by Kakkos et al used routine tourniquet derived cephalic vein measurements, the benefit of which remains unproven. 4 Though widely recommended, even duplex mapping did not improve functional AVF patency in a recent systematic review. 2 The study by Kakkos et al found that veins 4.2 mm had inferior functional patency for radiocephalic (RC)-AVF.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…7 The present study by Kakkos et al used routine tourniquet derived cephalic vein measurements, the benefit of which remains unproven. 4 Though widely recommended, even duplex mapping did not improve functional AVF patency in a recent systematic review. 2 The study by Kakkos et al found that veins 4.2 mm had inferior functional patency for radiocephalic (RC)-AVF.…”
mentioning
confidence: 98%
“…Early thrombosis accounted for only 5% with a multiplicity of aetiologies responsible for the remaining failures. 1,4 Research has focused on improving functional patency.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate fistula maturation might be closely associated with an optimal dilation of the brachial artery after fistula creation 10 . The brachial artery is usually the main feeding artery of the AVF, either directly (upper arm AVF), or through the radial artery (forearm AVF).…”
mentioning
confidence: 99%